2021
DOI: 10.1037/tra0000624
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation, coping, and PTSD in Hispanic 9/11 rescue and recovery workers.

Abstract: Objective: Research examining the responders of the World Trade Center terrorist attacks of 9/11 has found that Hispanic responders are at greater risk for posttraumatic stress disorder (PTSD) than non-Hispanic White responders. However, no studies have examined how acculturation may influence the relationship between coping and PTSD in Hispanic 9/11 responders. This novel study is the first to examine differences in coping and PTSD among Hispanic responders by level of acculturation. Methods: The sample is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…Acculturation is defined as the process in which an individual adopts, acquires, and adjusts to a new cultural environment ( 28 ). The degree of acculturation may relate to PTSD symptoms after traumatic events, as demonstrated in one study of Hispanic 9/11 responders in whom less acculturated participants had more severe PTSD ( 29 ). Given that our study recruited Spanish-speaking and English-speaking patients, our results likely reflect the lived experiences of a range of acculturation among Hispanics.…”
Section: Discussionmentioning
confidence: 99%
“…Acculturation is defined as the process in which an individual adopts, acquires, and adjusts to a new cultural environment ( 28 ). The degree of acculturation may relate to PTSD symptoms after traumatic events, as demonstrated in one study of Hispanic 9/11 responders in whom less acculturated participants had more severe PTSD ( 29 ). Given that our study recruited Spanish-speaking and English-speaking patients, our results likely reflect the lived experiences of a range of acculturation among Hispanics.…”
Section: Discussionmentioning
confidence: 99%
“…There are central moderator effects of culture, family and social networks, which buffer the impact of traumatic events on PTSD. In this view, Ciro et al (2021) report effects of culture in Hispanic rescue workers involved in 9/11 terrorist attacks, with less acculturated individuals suffering from more severe PTSD. Furthermore, meaningful differences arise regarding geographic location or occupational group, with a higher PTSD prevalence in workers from Asia and ambulance workers (Berger et al, 2012).…”
Section: Ptsd and Moderators In Rescue Workersmentioning
confidence: 99%
“…The importance of resilience as an inherent ability to manage daily stresses, as well as to overcome severe trauma, has increasingly been recognized [ 7 ]. Studies of frontline health care workers during the beginning of the COVID-19 pandemic and responders to the September 11, 2001, attacks have shown that resilience is important for both risk of PTSD and the ability to overcome trauma [ 8 , 9 ]. Further, researchers have made progress modeling the neurobiological components of resilience, pointing to both physiological processes and genetic factors that shape a person’s resilience [ 10 ].…”
Section: Introductionmentioning
confidence: 99%